(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The common clustering of glucose intolerance, abdominal adiposity, high triglyceride level, low highdensity lipoprotein cholesterol level and high blood pressure in a single individual is referred to as Metabolic Syndrome (MS) and it is associated with ischaemic heart disease (IHD). Objectives: To find out the relationship between MS and lHD. Design: Cross sectional observational study. Materials: 100 subjects were selected following simple random sampling technique. 50 patients of MS and another 50 non MS were enrolled as case and controlled respectively in the department of medicine and cardiology at Sylhet M.A. G. Osmani medical college hospital. Results: Proportion of IHD was found to be high among the MS (40%) compared to non MS (16%) and the difference was statistically significant (p=0.008) indicating there is a relationship between MS and lliD. Among the components of MS proportion of hypertension (39.2%), diabetes mellitus (41.9%), dyslipidernia (42.6%) and family history of cardiovascular disease (47.1 %) had significant higher association with patients with IHD (p<0.05). Conclusion: The MS has a significant association with IHD by electrocardiogram criteria.